Inhibition of Epidermal Growth Factor Receptor and PI3K/Akt Signaling Suppresses Cell Proliferation and Survival through Regulation of Stat3 Activation in Human Cutaneous Squamous Cell Carcinoma. (17th October 2010) - Bito, Toshinori; Sumita, Nahoko; Ashida, Masashi; Budiyanto, Arief; Ueda, Masato; Ichihashi, Masamitsu; Tokura, Yoshiki; Nishigori, Chikako
Abstract : Recent studies have emphasized the important role of Stat3 activation in a number of human tumors from the viewpoint of its oncogenic and antiapoptotic activity. In this study, we examined the role and related signaling molecules of Stat3 in the carcinogenesis of human cutaneous squamous cell carcinoma (SCC). In 35 human cutaneous SCC samples, 86% showed overexpression of phosphorylated (p)-Stat3, and most of those simultaneously overexpressed p-EGFR or p-Akt. Constitutive activation of EGFR and Stat3 was observed in three SCC cell lines and four of five SCC tissues. AG1478, an inhibitor of the EGFR, downregulated Stat3 activation in HSC-1 human SCC cells. AG1478 inhibited cell proliferation and induced apoptosis of HSC-1 cells but did not inhibit the growth of normal human epidermal keratinocytes that did not show Stat3 activation. Furthermore, a PI3K inhibitor also suppressed Stat3 activation in HSC-1 cells to some degree. Combined treatment with the PI3K inhibitor and AG1478 strongly suppressed Stat3 activity and dramatically induced apoptosis of HSC-1 cells. These data suggest that Stat3 activation through EGFR and/or PI3K/Akt activation plays a critical role in the proliferation and survival of human cutaneous SCC.